GUIDELINES FOR PREPARATION OF MANUSCRIPTS DESCRIBING CLINICAL CASES IN CHILDREN: SUPPORTING THE CARE AND SCARE PRINCIPLES - Ruslan T. Saygitov; Anastasiya S. Ostrovskaya (Вопросы современной педиатрии)
The guidelines for preparation of manuscripts describing clinical cases in children are presented. The guidelines are considered in a new editorial design standard which is presented in the template of the same name. The introduction of this standard will provide a detailed and consistent presentation of the results of medical supervision of patients and therefore the necessary quality of materials submitted for consideration to the editorial office.